2000
DOI: 10.1128/jb.182.5.1419-1422.2000
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calcium and Calcium Chelators on Growth and Morphology of Escherichia coli L-Form NC-7

Abstract: Growth of a wall-less, L-form of Escherichia coli specifically requires calcium, and in its absence, cells ceased dividing, became spherical, swelled, developed large vacuoles, and eventually lysed. The key cell division protein, FtsZ, was present in the L-form at a concentration five times less than that in the parental strain. One interpretation of these results is that the L-form possesses an enzoskeleton partly regulated by calcium.Numerous roles for calcium in bacteria are now becoming apparent (10,12,19)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 24 publications
1
37
0
Order By: Relevance
“…Divalent cations, and calcium in particular, stabilize the cell envelope through a number of mechanisms (10,39,50). For example, calcium may have a role in regulating the level of the key cell division protein FtsZ, which is often reduced in cell wall-defective mutants (40). Calcium and magnesium also help to stabilize the outer membrane through hydrostatic interactions with lipopolysaccharides (27,30,39,50).…”
Section: Discussionmentioning
confidence: 99%
“…Divalent cations, and calcium in particular, stabilize the cell envelope through a number of mechanisms (10,39,50). For example, calcium may have a role in regulating the level of the key cell division protein FtsZ, which is often reduced in cell wall-defective mutants (40). Calcium and magnesium also help to stabilize the outer membrane through hydrostatic interactions with lipopolysaccharides (27,30,39,50).…”
Section: Discussionmentioning
confidence: 99%
“…In microscopical studies serious cell alterations of the exposed F. psychrophilum were observed, most probably causing the decrease in the number of viable cells. In a previous study it was reported that lack of Ca 2+ causes spherical swelling, development of large vacuoles, and eventually lysis of Escherichia coli L-forms [10]. Both EDTA and EGTA chelates Ca 2+ , and in previous studies toxicity of these compounds to examined fish pathogenic bacteria (e.g.…”
Section: Treatment Of Serummentioning
confidence: 97%
“…In addition, they were observed in a number of E. coli shape mutants with ill-characterized lesions (2,3,38,54,63). Two of these older studies included thin section transmission electron microscopy analyses of the mutant cells.…”
Section: Suppression Of Mrdmentioning
confidence: 99%